Wired for Surgical Success: Our Experience with Preoperative Ultrasound-Guided Wire Localization of Impalpable Breast Lesions - Balakrishnan, Sanchanaa Sree; Dev, Bhawna; Gnanavel, Harini; Chinnappan, Sheela; Palanisamy, Priya; Hlondo, Lalchhanhimi (Indian Journal of Radiology and Imaging, 2021)
Aims The purpose of this study was to review our experience with preoperative ultrasound-guided wire localization and to identify our rate of successful localization and subsequent excision.Materials and Methods At our institution, we performed preoperative wire localization for 28 impalpable breast lesions in 27 women (1 patient underwent wire localization for bilateral breast lesions), between April 2016 and August 2019. We used a Toshiba APLIO2 ultrasound machine and a linear probe (7–12 MHz) to visualize lesions and needle-wire systems comprising a 20-gauge needle with preloaded wire to localize lesions. We analyzed the percentage of specimen mammograms with wire in situ and percentage of excised specimens showing margins free of tumor, along with imaging features, BI-RADS (Breast Imaging-Reporting and Data System) categories, and histopathological and molecular diagnosis of the lesions.Results All specimen mammograms confirmed the presence of wire in situ, except one (96.4%); in the latter case, postponement of surgery due to intractable cough was suspected to have caused wire displacement. All malignant specimens showed margins free of tumor (100%).Conclusions Our results show that wire localization is extremely effective in providing crucial preoperative insight into the precise location of an impalpable lesion. Despite the advent of nonwire localization devices such as radioactive seeds, radar reflectors, magnetic seed markers, and radiofrequency identification tags, wire localization remains the most widely practiced method, especially in resource-limited settings. Its high degree of accuracy serves as a key factor in the successful outcome of breast conservation surgery for impalpable breast lesions.
Keywords: breast; impalpable; ultrasound-guided; wire localization